Color-spectrum-broadened ductile cellulose films for vapor-pH-responsive colorimetric sensors - Yang, Hakyeong; Choi, Song-Ee; Kim, Doyeon; Park, Daehwan; Lee, Duho; Choi, Sunyoung; Nam, Yoon Sung; Kim, Jin Woong (Journal of industrial and engineering chemistry (Seoul, Korea), 2019)
[Display omitted] •A vapor-pH-responsive smart cellulose nanocrystal (CNC) film sensor system is proposed.•Utilization of oxidized CNCs with controlled amounts of surface charges enabled regulation of the pitch distance during film formation.•Ductile CNCs films showed reversible color changes in response to vapors of aqueous solutions with different pH values. We introduce a smart colorimetric sensor platform, in which iridescent chiral nematic films composed of oxidized cellulose nanocrystals (OxCNCs) exhibit pH-responsive color changes. To provide dried OxCNC films with the controlled reflection of circularly polarized lights at specific wavelengths, we manipulated the half-pitch distance from 145 to 270nm by adjusting the surface charges of OxCNCs during 2,2,6,6-tetramethylpiperidine-1-oxyl-radical-mediated oxidation. Utilizing the controlled electrostatic repulsion generated by the difference in the surface charge of OxCNCs, the reflection wavelengths of the films could be tuned across a broad color spectrum. In addition, we improved flexibility or ductility of OxCNC composite films by coassembly with a hygroscopic polymer, polyethylene glycol, while maintaining their iridescent colors. We finally demonstrated that the OxCNC composite films could show reversible color changes in response to vapors of aqueous solutions with different pH values, thus enabling the development of a vapor-pH-responsive colorimetric sensor technology.